Relationships between parameters of gallbladder motility and brain electrical activity - Marfiyan, Olena M; Zukow, Walery; Popovych, Milentyna V; Ganyk, Lyubov M; Kit, Yevgen I; Ivanyts’ka, Oksana M; Kyjenko, Valeriy M (Journal of Education, Health and Sport, 2016)
Marfiyan Olena M, Zukow Walery, Popovych Milentyna V, Ganyk Lyubov M, Kit Yevgen I, Ivanyts’ka Oksana M, Kyjenko Valeriy M. Relationships between parameters of gallbladder motility and brain electrical activity. Journal of Education, Health and Sport. 2016;6(8):11-20. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.59271 http://ojs.ukw.edu.pl/index.php/johs/article/view/3728 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.07.2016. Revised 25.07.2016. Accepted: 28.07.2016. RELATIONSHIPS BETWEEN PARAMETERS OF GALLBLADDER MOTILITY AND BRAIN ELECTRICAL ACTIVITY Olena M Marfiyan1,2, Walery Zukow3, Milentyna V Popovych4, Lyubov M Ganyk4, Yevgen I Kit4, Oksana M Ivanyts’ka1, Valeriy M Kyjenko5 1JSC “Truskavets’kurort”, Truskavets’, Ukraine olenka80@meta.ua 2Department of Pediatry, OO Bohomolets’ National Medical University, Kyiv, Ukraine 3Faculty of Physical Education, Health and Tourism, Kazimierz Wielki University, Bydgoszcz, Poland w.zukow@ukw.edu.pl 4Center of Medical Rehabilitation and Spa Cure “Truskavets’kyǐ” War Ministry, Truskavets’, Ukraine 5Laboratory of Experimental Balneology, OO Bohomolets’ Institute of Physiology NAS, Kyiv, Ukraine i.popovych@biph.kiev.ua Abstract Objective. Earlier we shown that Cholecystokinetic effect of balneotherapy on spa Truskavets’ may be the result of modulation of neuroendocrine-immune complex. The aim of present investigation: clarification relationships between parameters of gallbladder motility and ongoing Electroencephalogram (EEG) as well as Heart Rate Variability (HRV). Material and Methods. At 22 men with chronic cholecystite combined with pyelonephrite we recorded twice basal and postprandial volume of gallbladder (Echoscopy by “Radmir”), EEG ("NeuroCom Standard") and HRV ("CardioLab+HRV"). Results. Basal gallbladder volume correlated positively with HRV markers of Vagal tone (HF, RMSSD, pNN50) and relative Power Spectrum Density (PSD) C4-δ while negatively with Amplitude of β-Rhythm and its absolute PSD in loci P3, P4, Fp1, C3, F3, F4 as well as PSD T3-δ and Frequency of α-Rhythm. Canonical correlation is very strong: R=0,96; Adjusted R2=0,85; χ 2(15) =61; p<10-5. Gallbladder volume after 5 min after taking of Cholekinetik (50 ml of 40% solution of xylitol), expressed as portion its basal volume, correlated positively with VLF, Deviation of θ-Rhythm and its relative PSD in loci F4, P4 and P3 while negatively with relative PSD O1-θ and absolute PSD P4-β and T6-β as well as Asymmetry of θ-Rhythm. Canonical correlation is very strong too: R=0,87; Adjusted R 2 =0,66; χ 2(9) =38; p<10 -4 . As distinct from early next postprandial volumes significantly less liable to neural regulatory influences: R makes 0,67 (p=0,003) and 0,60 (p=0,009) after 15 and 30 min respectively. In particular, both V15 and V30 equal positively correlated with HF and Laterality of α-Rhythm, however V15 correlated with Asymmetry of θ-Rhythm (r=-0,45) and its PSD in loci F3 (r=0,28) and C4 (r=0,27), while V30 correlated with Asymmetry of δ-Rhythm (r=-0,28) and PSD C4-β (r=-0,34). Conclusion. Fasting gallbladder volume is strong controlled by Vagal nerves as well as by neural structures generating β-Rhythm, whereas early (5 min) postprandial volume is also strong controlled by structures generating θ-Rhythm. Next (15 and 30 min) postprandial volumes significantly less liable to neural regulatory influences. Keywords: gallbladder motility, EEG, HRV, relationships.